How do apples grow? - Maestro, Betsy; Maestro, Giulio (New York, NY : HarperCollins, 1992)
Describes the life cycle of an apple from its initial appearance as a spring bud to that point in time when it becomes a fully ripe fruit
550
Accelerated Reader AR
Keywords: Apples; Plants -- Development